Implementation of sound perception elements for visually impaired people in collaborative and synchronous Web systems - Machado, Rodrigo Prestes Machado; Conforto, Débora Conforto; Santarosa, Lucila Santarosa; Keywords, Author Keywords (Teste; 2018: IHC_19, 2019)
This paper discusses the implementation of accessibility features for visually impaired people in synchronous and collaborative systems on the Internet. Based on the sociocultural scenario of affirmation of difference and in the contexts of cooperation established by Web 2.0, we discuss the application of sound awareness elements in Groupware tools through Auditory Icons, Earcons and synthesized speech in a web chat system. It is characterized as a qualitative, experimental research with internal data validation and an exploratory objective. The process of data collection and analysis was conducted through protocols applied with a real user. The results of the experiments showed a good adherence of these technologies in the construction of sound awareness elements to screen reader users.